Non-steady FE analysis on porthole dies extrusion of aluminum harmonica-shaped tube - 程磊 谢水生 黄国杰 吴朋越 和优锋 (Transactions of Nonferrous Metals Society of China, 2007)
According to the rigid-viscoplasticity finite element method, the porthole die extrusion process of an aluminum harmonica-shaped tube was successfully simulated based on software Deform-3D. The distribution of stress field, effective strain field, velocity field and temperature field during the extrusion process were discussed and the metal flow in welding extrusion was analyzed. The simulation results show that the material flow velocities in the bearing exit are non-uniform with the originally designed die and the forepart of the profile is not neat or even. Aiming at solving this problem, the modification method of die structure was improved. The result shows that the uniform material flow velocities in the die exit and a perfect extruded are obtained by modification bearing length.